Online style – poking a hornet’s nest - Allan Lee (Asia Pacific Network, 2013)
Writing news for newspapers and websites typically demands conformity to a style that promotes clarity and ease of reading, and includes a publication’s house style, that inflexible set of rules that ensures things—from minutiae like monetary values to the great events of history—are expressed consistently every time they are mentioned. Against a background of disruptive technological changes in the wider world of journalism, this article grew out of the authors’ interest in the new style demands that arguably have arisen with the advent of online publishing. If online readers have a different set of habits—and researchers assure us they do—then how is house style being changed to accommodate this? Are newspapers with websites differentiating their online copy from their print copy? Or are they still stuck with so-called ‘shovelware’? Keen to ensure the university production journalism courses on which they teach are reflecting industry practice, the researchers surveyed and interviewed reporters, subeditors and editors from titles across Australia and New Zealand to find out, and interviewed the online editor of NZ’s largest newspaper. The research supports our hypothesis—that newsrooms are aware of a need to develop style guidelines for their online news stories but most have yet to truly grapple with the issue.